Search for anomalous t(t)over-bar production in the highly-boosted all-hadronic final state - Chatrchyan, S; Khachatryan, V; Sirunyan, A; Tumasyan, A; Adam, W; Bergauer, T; Dragicevic, M; Eroe, J; Fabjan, C; Friedl, M; Fruehwirth, R; Ghete, V; et al. (2012)
A search is presented for a massive particle, generically referred to as a Z', decaying into a tt̄ pair. The search focuses on Z' resonances that are sufficiently massive to produce highly Lorentz-boosted top quarks, which yield collimated decay products that are partially or fully merged into single jets. The analysis uses new methods to analyze jet substructure, providing suppression of the non-top multijet backgrounds. The analysis is based on a data sample of proton-proton collisions at a center-of-mass energy of 7 TeV, corresponding to an integrated luminosity of 5 fb -1. Upper limits in the range of 1 pb are set on the product of the production cross section and branching fraction for a topcolor Z' modeled for several widths, as well as for a Randall-Sundrum Kaluza-Klein gluon. In addition, the result contrain any enhancement in tt̄ production beyond expectations of the standard mode for tt invariant mass larger than 1TeV/c 2.